2003
DOI: 10.1093/carcin/bgh031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of soy isoflavones on rat prostate carcinogenesis induced by 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)

Abstract: Intake of isoflavones derived from soybean products may impact on prostate cancer risk. Here we evaluated the effects of Fujiflavone, a commercial isoflavone supplement, on rat prostate carcinogenesis induced by 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), the most abundant heterocyclic amine in cooked meat. F344 male rats were given intragastric administrations of PhIP at the dose of 200 mg/kg twice weekly for 10 weeks. The rats subsequently fed a diet containing 0.25% Fujiflavone showed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Ligand-binding studies have shown that ER␤ exhibits a 40-fold higher affinity for genistein than does ER␣, suggesting that this compound may act through ER␤-signaling pathways (32). In the rat prostate, isoflavones up-regulate heat shock protein HSP-27 and inhibit progression of PIN to adenocarcinoma (33). Because ER␤ is the only ER in the prostate, and heat shock protein HSP-27 is known to be induced by estrogen (34), it is tempting to speculate that isoflavones might act through ER␤.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-binding studies have shown that ER␤ exhibits a 40-fold higher affinity for genistein than does ER␣, suggesting that this compound may act through ER␤-signaling pathways (32). In the rat prostate, isoflavones up-regulate heat shock protein HSP-27 and inhibit progression of PIN to adenocarcinoma (33). Because ER␤ is the only ER in the prostate, and heat shock protein HSP-27 is known to be induced by estrogen (34), it is tempting to speculate that isoflavones might act through ER␤.…”
Section: Discussionmentioning
confidence: 99%
“…Prepubertal exposure to soy or genistein reduced mammary carcinogenesis in rats treated with carcinogens, possibly by modulating the development of the mammary end buds (2). Various soy products containing genistein have been found to inhibit the growth of transplanted human prostate carcinoma, reduce the incidence of poorly differentiated prostate adenocarcinoma in a transgenic mouse model, and inhibit 2-amino-1-methyl-6-phenylimidazo [4,5]pyridine-induced rat prostate carcinogenesis (3). Carcinogenesis or metastasis in the stomach, colon, bladder, and lung is also inhibited by genistein and related isoflavones (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Various soy products containing genistein have been found to inhibit the growth of transplanted human prostate carcinoma, reduce the incidence of poorly differentiated prostate adenocarcinoma in a transgenic mouse model, and inhibit 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridineinduced rat prostate cancer (36). Carcinogenesis or metastasis to the stomach, colon, bladder, and lung is also inhibited by genistein and related isoflavones (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%